Evaluation of a Mechanistic Model and Finite Element Analysis for Geosynthetic-Reinforced Sub-grade Material Performance Under Cyclic Loading - RamazanBorujerdi, Ali (Journal of Science and Technology, 2024)
This study investigates the outcomes of triaxial repeated loading tests on geosynthetic reinforced base course materials intended for road construction. Triaxial testing was utilized to simulate the impact of traffic loads. Two types of samples were examined: one set without reinforcement and another with reinforcement. The research included a thorough series of tests that varied parameters such as density, moisture content, initial effective stress, and cyclic loading conditions. The findings can be illustrated through deformation and failure envelopes applicable to various cycle counts. Factors such as the material’s compaction level, moisture content, and saturation degree significantly affect its deformability. An elastic-plastic analysis utilizing the finite element method (FEM) was conducted to validate the experimental results and to establish the parameters necessary for the FEM analysis of the pavement. Utilizing the principles outlined in the AASHTO pavement design methodology, the necessary combined load-bearing capacity of the pavement layers situated above the sub-grade was determined. Additionally, the AASHTO geosynthetic reinforced roadway design approach was established. The mechanical properties, specifically strength and stiffness of reinforced with geosynthetics at various elevations were assessed through both static and cyclic triaxial testing methods. It was noted that the positive impacts of reinforcement were closely linked to the amount of reinforcement used, with the advantages of geosynthetic reinforcement becoming particularly apparent at higher strain levels.